Detection of B. anthracis from Environmental Samples during Outbreak in Tamilnadu by Molecular Methods - Senthilkumar, K.; Ravikumar, G.; Tirumurugaan, K. G. (International Journal of Bio-resource and Stress Management, 2022)
The study was undertaken during 2013−2017 at Zoonoses Research Laboratory, Tamil Nadu Veterinary and Animal Sciences University, Chennai. Blood smears, soil and environmental samples were collected from 23 sporadic incidences of anthrax reported in different parts of Tamil Nadu from 2013−2017. 11 incidences were presumptively diagnosed as anthrax by detecting capsulated bacilli on polychrome methylene blue staining and microscopy. The spores in soil samples (62) were extracted, cultured and DNA was extracted for molecular method of diagnosis. The molecular method detected twelve incidences as anthrax by amplifying the virulence factors like lef gene (385bp) and capsular gene (264bp) encoded in pXO1 and pXO2 plasmids respectively and chromosomal marker (Ba813) gene (152bp) using multiplex PCR. The partial sequence of cap gene of isolates (Vellore and Nolambur strain) revealed a close relationship with B. anthracis species. The relatedness of the isolated strains to virulent strains such as Ames and Vollum strain on phylogenetic analysis showed the nature of the outbreak. Since the multiplex PCR detects the outbreak with short turn-around time by detecting both chromosomal and Plasmid DNA, considered as a confirmative diagnosis. Further the molecular method of diagnosis precludes the need for culturing thereby avoiding unnecessary occupational risks and environmental contamination.